1996
DOI: 10.1080/00221325.1996.9914849
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Perceptions of Children's Worries in a Changing World

Abstract: The nature and intensity of worries that preadolescent children experience and the extent to which parents are aware of their children's concerns were examined. Questionnaires with three subscales (Physical Harm, Daily Life Matters, and Global Issues) were filled out by 89 6th graders and their parents. Parents underestimated the overall degree to which children worry, and they tended to believe that their children worried most about daily life matters, such as grades and popularity; children were in fact leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Female children tend to report higher levels of worry compared to male children Muris et al 2001), and this pattern has been documented in children as young as 7 years (Silverman et al 1995). Parent report corroborates children's self-report findings, indicating that mothers believe their daughters worry more than their sons (Gottlieb and Bronstein 1996). Another study found that girls reported more specific worries than boys and also endorsed more physical symptoms than boys .…”
Section: Sexsupporting
confidence: 54%
“…Female children tend to report higher levels of worry compared to male children Muris et al 2001), and this pattern has been documented in children as young as 7 years (Silverman et al 1995). Parent report corroborates children's self-report findings, indicating that mothers believe their daughters worry more than their sons (Gottlieb and Bronstein 1996). Another study found that girls reported more specific worries than boys and also endorsed more physical symptoms than boys .…”
Section: Sexsupporting
confidence: 54%
“…However, one study failed to find significant statistical differences between boys and girls, despite a few trends [13]. The gender differences in worry seem to be sustained by parent reports too, as mothers believe their daughters worry more than their sons [25].…”
Section: Worry Differences Across Gendermentioning
confidence: 84%
“…Children daily life is something that children know the most about. Studies have found that parents do not really know how children spend their time (Funk et al, 1999) or what they are worried about (Gottlieb and Bronstein, 1996) . Hence to answer such questions in the best possible way we need the children to be involved in the studies, at least as our primary source of information.…”
Section: The Consequences Of the Changing Fieldmentioning
confidence: 98%